Single machine scheduling with slack due dates assignment. Issue 4 (3rd April 2017) - Liu, Weiguo; Hu, Xiangpei; Wang, Xuyin
ABSTRACT: This paper considers a single machine scheduling problem in which each job is assigned an individual due date based on a common flow allowance ( i.e. all jobs have slack due date). The goal is to find a sequence for jobs, together with a due date assignment, that minimizes a non-regular criterion comprising the total weighted absolute lateness value and common flow allowance cost, where the weight is a position-dependent weight. In order to solve this problem, an time algorithm is proposed. Some extensions of the problem are also shown.